Risky foods, safer choices : avoiding food poisoning / Peter Cerexhe, John Ashton - Cerexhe, Peter
Risky Foods, Safer Choices confirms what many people may have suspected - the incidence of food poisoning is on the rise. Triggering such public suspicions has been an ongoing procession of horror incidents involving such foods as salami, oysters, pork rolls, fruit salad and even orange juice that have resulted in the serious illness and even death of consumers. Risky Foods, Safer Choices helps consumers avoid the possibly tragic consequences of food poisoning. Its focus is on relatively short-term health effects of good food selection rather than longer-term health effects.